The Impact of Exchange Rate Volatility on Credit Risk in South African Banking Portfolios: Credit risk - Magwedere, Margaret Rutendo; Chisasa, Joseph (Acta Universitatis Danubius. Œconomica, 2023)
Macroeconomic shocks affect loan defaults in the credit markets. The South African rand has been volatile with low economic growth and high unemployment. Time series data from 2008Q1-2018Q4 was used to determine the impact of exchange rate on credit risk in South African banking portfolios. Cointegration and error correction model were applied to determine the impact of selected macroeconomic variables on credit risk. Macroeconomic shocks significantly affect bank asset quality. A 1% increase in exchange rate increases impaired loans by 0.57%. Banking sector stability is essential; hence, policymakers should understand macroeconomic fundamentals that significantly affect bank asset quality.